Analysis of C9orf72 repeat expansions in a large international cohort of Dementia with Lewy Bodies - Kun-Rodrigues, Celia; Ross, Owen A.; Orme, Tatiana; Shepherd, Claire; Parkkinen, Laura; Darwent, Lee; Hernandez, Dena; Ansorge, Olaf; Clark, Lorraine N.; Honig, Lawrence; Marder, Karen; Lemstra, Afina; et al. (Elsevier, 2016)
C9orf72 repeat expansions are a common cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). To date, no large-scale study of dementia with Lewy bodies (DLB) has been undertaken in order to assess the role of C9orf72 repeat expansions in the disease. Here we investigated the prevalence of C9orf72 repeat expansions in a large cohort of DLB cases and identified no pathogenic repeat expansions in neuropathologically or clinically defined cases, showing that C9orf72 repeat expansions are not causally associated with DLB.